Efficiency of attentional processes in attention network theory and autistic symptoms in adolescents with autism spectrum disorder - Pudło, Monika; Pisula, Ewa (Frontiers in Psychiatry, 2022)
Background. Attentional impairments in children with Autism Spectrum Disorder (ASD) have been studied extensively, particularly in toddlers and young children. Attentional processes in teenagers with ASD are not fully understood, nor are the relationships between attentional deficits and ASD symptoms in this group. Method: The aim of this study was to measure the attentional characteristics that attention network theory posits as being related to attention processes: alerting, orientating, and executive attention. We included 37 adolescents (aged 12–20) with ASD and Wechsler IQ in the normal range (≥70) and 37 neurotypical counterparts (NT) matched in terms of age, gender, and IQ. Symptoms of ASD were measured using the Autism Diagnostic Observation Schedule – Second Edition (ADOS-2) and Autism Diagnostic Interview – Revised (ADI-R). Results: The adolescents with ASD reacted more slowly in all task conditions of the Attention Network Test and committed more errors in six of seven task conditions of this test. There were no group differences in the effects of alerting, orienting, and executive attention. We found moderate correlations of the effect of executive attention with three scales of ADOS-2 (communication, social functioning, and restricted behavior), as well as with the social scale and restricted behavior of ADI-R. Conclusions: The results indicate that adolescents with ASD performed tasks requiring alerting and orienting attention less efficiently than their counterparts in terms of correctness and reaction time. The relationships between executive attention measures and communication and social affect is discussed.